Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ijmm.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory bacterial pathogens causing atypical pneumonia by multiplex Lightmix ® RT-PCR

Abstract: Pneumonia is a severe infectious disease. In addition to common viruses and bacterial pathogens (e.g. Streptococcus pneumoniae), fastidious respiratory pathogens like Chlamydia pneumoniae, Mycoplasma pneumoniae and Legionella spp. can cause severe atypical pneumonia. They do not respond to penicillin derivatives, which may cause failure of antibiotic empirical therapy. The same applies for infections with B. pertussis and B. parapertussis, the cause of pertussis disease, that may present atypically and need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Among the 18 PCR-diagnosed cases for which a UAT was performed, only 2 showed positive UAT results, which implied that 16 of these PCR-diagnosed cases would not have been diagnosed if PCR had not been performed. With the development of commercially available multiplex PCR assays for respiratory pathogens, including Legionella species ( 12 ), it is expected that the Legionnaires’ disease incidence will continue to increase, and the percentage of Legionnaires’ disease cases diagnosed by PCR will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 18 PCR-diagnosed cases for which a UAT was performed, only 2 showed positive UAT results, which implied that 16 of these PCR-diagnosed cases would not have been diagnosed if PCR had not been performed. With the development of commercially available multiplex PCR assays for respiratory pathogens, including Legionella species ( 12 ), it is expected that the Legionnaires’ disease incidence will continue to increase, and the percentage of Legionnaires’ disease cases diagnosed by PCR will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…Another multiplex PCR, Fast Track Diagnostics FTD-29.19, tests nine bacterial pathogens and has demonstrated more pathogen detection in 37 per cent over 11 per cent by conventional methods in elderly patients 87 . Multiplexing several gene targets for detection of atypical pathogens has shown comparable performance with in-house individual PCRs in a study demonstrating overall 52 per cent PCR positivity in patients suspected with atypical pneumonia 88 .…”
Section: Microbiological Diagnostics In Cabp-bridging Ideal and Real mentioning
confidence: 99%
“…ICU, intensive care unit; PCR, polymerase chain reaction. Source : Refs 29 38 54 58 59 82 85 86 88 .…”
Section: Microbiological Diagnostics In Cabp-bridging Ideal and Real mentioning
confidence: 99%
“…10,20,22 We believe that this variation is related to the collection method and site of the specimens subjected to PCR testing. The diagnostic performance of Roche Mycoplasma pneumoniae, Chlamydia pneumoniae, and Legionella pneumophila multiplex Lightmix RT-PCR kit has been evaluated by Wagner et al 23 and showed identical performance characteristics (specificity and sensitivity) to in-house singleplex RT-PCRs for pathogen detection. Wagner 24 and Orozco-Hoyos 25 used the kit to detect Mycoplasma pneumoniae, Chlamydia pneumoniae.…”
Section: Discussionmentioning
confidence: 99%